Chemical composition and antimicrobial activity of Satureja montana byproducts essential oils - Santos, Jéssica D.C. (2021)
Satureja montana is a worldwide consumed aromatic plant whose essential oils (EOs) are used as spice and preservative by food industry. Only the leaves are marketed, generating a large amount of stems as byproducts. It is possible that the EOs present in these byproducts represent a source of compounds with antimicrobial activity, as observed for the leaves. In this work, dried S. montana byproducts were used to extract EOs. Although differences were observed for the harvest year (0.42 ± 0.11 mg/g in 2016 and 0.14±0.07 mg/g in 2017), monoterpenoids were the major components, accounting for 84.4 to 97.6%, being carvacrol the most abundant component (825 – 950 μg/mg). Sesquiterpenoids accounted for 0.3 to 0.5%. Similar EOs yield and composition were obtained using solvent-free microwave extraction (16 min using 100 g of S. montana stems, previously, soaked in water and drained) or hydrodistillation (120 min using 1000 mL of water/ 100 g of dried S. montana stems). The in vitro minimal inhibitory concentrations (MICs) of S. montana EOs against Escherichia coli ATCC 25922, Salmonella enterica sv Anatum SF2, and Staphylococcus aureus ATCC 6538, which belong to pathogenic species with economic impact in poultry industry, were 225 μg/mL, 250 μg/mL, and 150 μg/mL, respectively. As these MICs are similar to the ones reported for carvacrol against the same or related strains, it can be concluded that carvacrol is the active compound in S. montana byproducts.